Printing a Document Remotely Using Print on a Click Technology - Kungwani, Amrita; Rukhsar, Mirza; Mansach, Surjit (International Journal of Computer Sciences and Engineering, 2025)
Mobile printing is the process of sending data to a printer wirelessly from a smart phone or tablet. There are two main approaches to mobile printing. The other approach involves communication between a mobile device and a computer connected to a printer. While a mobile phone is simply not just a phone these days, the numbers of applications are building on a wide range of platforms for mobile phone is astounding. Wireless means transmitting signals using radio waves as the medium instead of wires and with the help of air medium. A Wireless network has offers the whole world an alternative solution for such problem of information access. Today wireless is very popular technology that is giving shape to more convenient and cost-effective world. Wireless printing using mobile devices is gaining popularity and this paper aims to address this particular functionality from Android Application. The Raspberry Pi is a low cost single-board computer which has recently become very popular. In this paper we showcase our attempt at building a low cost stand-alone device which transmits data using the Raspberry Pi with WI-FI and has a resistive touch screen display providing a user interface